Prognostic Significance of β-Catenin Expression in Osteosarcoma: A Meta-Analysis - Xie, Xiaoliang; Li, Yumei; Zhu, Haixia; Kuang, Zhixing; Chen, Deta; Fan, Tianyou (Frontiers in Oncology, 2020)
Background: β-catenin plays a crucial role in the progression of osteosarcoma. However, the clinical significance of β-catenin over-expression in osteosarcoma still remains unclear. Thus, we performed a meta-analysis of studies that evaluated the impact of β-catenin on metastasis and overall survival (OS) in osteosarcoma. Methods: We searched PubMed, The Cochrane Library, Embase, Springer, Science Direct, OVID, Weipu, Wanfang and China National Knowledge Internet(CNKI) databases from their start year up to Aug.2019. Individual hazard ratios (HRs) and 95% confidence intervals (CIs) were extracted and pooled HRs with 95% CIs or odd ratio (OR) were used to evaluate the relationships between β-catenin over-expression and metastasis and overall survival in osteosarcoma. Results: Eight related studies involving 521 patients were qualified for this meta-analysis. Results showed that over-expression of β-catenin was significantly correlated with metastasis (OR=3.31, 95% CI=2.08-5.24, P<0.001) and overall survival (HR=2.32, 95% CI =1.48-363, P=0.02). Conclusion: The meta-analysis revealed that over-expression of β-catenin might be associated with distant metastasis and overall survival in osteosarcoma, which reminds that β-catenin acts as a prognostic biomarker and it can guide the clinical therapy in osteosarcoma patients.